(untitled) (Nigerian Journal of Technology, 2018)
The flux-linkage characteristics of dual excited permanent magnet (PM) machines equipped with concentrated windings of single- and double-layer types is investigated in this paper. This includes precise comparison of the coil and phase flux-linkage waveforms of the machines having different stator and rotor pole topologies. It is observed that, the developed machine having double layer-wound configuration have unipolar coil flux linkage waveforms, although with a resultant bipolar phase flux-linkage waveforms on summation, while their corresponding single layer-wound counterparts are characterised by both bipolar coil and phase flux-linkage waveforms. Also, the opposite coils of the machines having single-layer windings as well as even rotor pole topology produces coil flux-linkage waveforms whose shape and magnitude are identical and same; thus, resulting to more phase harmonics unlike their counterparts that are equipped with odd rotor poles and single-layer winding configuration whose coil waveforms are shifted, thereby resulting to effective cancellation of harmonics in the resultant phase waveforms. In general, the single-layer-wound machines exhibit higher peak-to-peak and fundamental flux-linkage values than their double-layer-wound equivalents. http://dx.doi.org/10.4314/njt.v37i3.27